Acceleration of the head during alpine skiing - Swaren, M.; Danvind, J.; Holmberg, H. C. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: The effects of skiing helmets have been studied previously. However, to our knowledge no studies have investigated forces and muscular work acting on a skier's neck during alpine skiing. The main purpose with this study was to develop a method to investigate accelerations of the head and manubrium sterni (MS) during alpine skiing, in order to simulate muscular forces on the neck and cervical spine